Functional Characterization of the Arabidopsis Abscisic Acid Transporters NPF4.5 and NPF4.6 in Xenopus Oocytes - Léran, Sophie; Noguero, Mélanie; Corratgé-Faillie, Claire; Boursiac, Yann; Brachet, Chantal; Lacombe, Benoit (Frontiers in Plant Science, 2020)
Few proteins have been characterized as ABA transporters. Several of them are NPF transporters which have been characterized in yeast using reporter systems. Because several members of the NPF4 subfamily members were identified in yeast as ABA transporters, here, we screened for ABA transport activity the seven members of the NPF4 subfamily in Xenopus oocytes using cRNA injection and 3H-ABA accumulation. The ABA transport capacities of NPF4.2; NPF4.5, NPF4.6 and NPF4.7 were confirmed. The transport properties of NPF4.5 and NPF4.6 were studied in more details. Both ABA transporters activity are pH-dependent and slightly pH-dependent apparent Km around 500 M. There is no competitive inhibition of the ABA-analogs pyrabactin and quinabactin on ABA accumulation demonstrating a different selectivity compared to the ABA receptors. Functional expression of these ABA transporters in Xenopus oocyte is an opportunity to start structure-function studies but also to identify partner proteins of these hormones transporters.